Pengetahuan Tentang Kesehatan Gigi Dan Mulut Pada Siswa Kelas IV SD Negeri Baratajaya Surabaya - Puspita Maharani Rezky Adynur; Silvia Prasetyowati; Imam Sarwo Edi (Poltekkes Kemenkes Surabaya, 2023)
ABSTRACT Introduction : Dental and oral health in the Indonesian population must receive serious attention especially in school children. The Basic Health Research (Riskesdas) of the Ministry of Health of the Republic of Indonesia in 2018 stated that as many as 55.6% of the group of school children aged 10-14 years experienced problems with dental and oral health and only 9.4% had received treatment from medical personel. Problem : a problem in this study is the average value of DMF-T in the medium category in Grade IV Students of SD Negeri Baratajaya Surabaya. The Purpose : The purpose of this study is to know the description of knowledge about dental and oral health in class IV SD Negeri Baratajaya Surabaya. Methods : This research is a descriptive research that implemented on January 2023 and involved 94 respondents, which was carried out by giving a questionnaire. The data analysis technique used is by recap the results of the data that has been collected and presented in tabular form. Results : Based on the results of the research, it was found that the knowledge of fourth grade students at SDN Baratajaya Surabaya about dental and oral diseases was included in the enough category, as well as knowledge about how to maintain dental and oral health was included in the enough category. Conclusion : The knowledge of fourth grade students at SDN Baratajaya Surabaya about oral health is in the enough category